Associations among child abuse history, deployment‐related traumatic events, mental disorders, and suicidal behaviors in Canadian Regular Force personnel. Issue 4 (21st June 2022) - Taillieu, Tamara L.; Sareen, Jitender; Afifi, Tracie O.
Abstract: Increasing attention has been focused on suicidal behavior among military personnel. Exposure to deployment‐related traumatic events (DRTEs) and child abuse (CA) both have been associated with mental disorders and suicidal behaviors among military personnel. Thus, the primary objectives of this study were to examine (a) sex differences in CA history and DRTEs, past‐year mental disorders, and past‐year suicide‐related outcomes and (b) independent, cumulative, and interactive effects of CA history and DRTEs on past‐year mental disorders and suicide outcomes among Canadian military personnel. Data were from the representative Canadian Forces Mental Health Survey collected in 2013 ( N = 8, 161; response rate = 79.8%). The results indicated a high prevalence of trauma exposure, with sex differences noted for specific trauma types. Both CA history and DRTEs were strongly associated with mental disorders, CA history: a OR s = 1.60–2.44; DRTEs; a OR s = 1.67–3.88. Cumulative, but not interactive, effects were noted for the effects of CA history and DRTEs on most mental disorders. Associations between CA history and DRTEs on suicide outcomes were largely indirect via their impact on mental disorders. Information regarding the role of specific types of predeployment trauma on mental disorders and suicidal behavior can be used to develop more targeted prevention and intervention strategies aimed at improving the mental health of military personnel.